2014
DOI: 10.1039/c4cp00935e
|View full text |Cite
|
Sign up to set email alerts
|

Advanced unidirectional photocurrent generation via cytochrome c as reaction partner for directed assembly of photosystem I

Abstract: Conversion of light into an electrical current based on biohybrid systems mimicking natural photosynthesis is becoming increasingly popular. Photosystem I (PSI) is particularly useful in such photo-bioelectrochemical devices. Herein, we report on a novel biomimetic approach for an effective assembly of photosystem I with the electron transfer carrier cytochrome c (cyt c), deposited on a thiol-modified gold-surface. Atomic force microscopy and surface plasmon resonance measurements have been used for characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 44 publications
1
79
0
4
Order By: Relevance
“…It has been shown that the isolated RC can bind (up to) 24 molecules of cyt c , 43 and the PSI RC has been shown to promote the coadsorption of electroactive cyt c to form multilayers on electrode surfaces. 21 It is likely that we have a similar semi-multilayer architecture on our electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the isolated RC can bind (up to) 24 molecules of cyt c , 43 and the PSI RC has been shown to promote the coadsorption of electroactive cyt c to form multilayers on electrode surfaces. 21 It is likely that we have a similar semi-multilayer architecture on our electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…42 This is also similar to the reported Γ cyt c on a mSAM of the same composition used in this work. 21 This ideal loading was multiplied by a reported 21-fold surface area increase for a rough silver electrode versus a flat silver electrode to obtain 320 pmol cm –2 . 36 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It attracts growing interest for designing biophotoelectrochemical devices [7][8][9][10][11][12][13] due to its remarkable charge separation functionality and close to perfect quantum yield of almost unity. 14 The combination of PS1 and Os-complex modified redox polymers has been exploited for photocurrent generation.…”
mentioning
confidence: 99%